In-line filtration reduced phlebitis associated with peripheral venous cannulation: Focus on cost-effectiveness and patients' perspectives. Issue 2 (March 2020) - Villa, Gianluca; Giua, Rosa; Amass, Timothy; Tofani, Lorenzo; Chelazzi, Cosimo; Pinelli, Fulvio; De Gaudio, A Raffaele; Romagnoli, Stefano
Background: In a previous trial, in-line filtration significantly prevented postoperative phlebitis associated with short peripheral venous cannulation. This study aims to describe the cost-effectiveness of in-line filtration in reducing phlebitis and examine patients' perception of in-hospital vascular access management with and without in-line filtration. Methods: We analysed costs associated with in-line filtration: these data were prospectively recorded during the previous trial. Furthermore, we performed a follow-up for all the 268 patients enrolled in this trial. Among these, 213 patients responded and completed 6 months after hospital discharge questionnaires evaluating the perception of and satisfaction with the management of their vascular access. Results: In-line filtration group required 95.60€ more than the no-filtration group (a mean of € 0.71/patient). In terms of satisfaction with the perioperative management of their short peripheral venous cannulation, 110 (82%) and 103 (76.9%) patients, respectively, for in-line filtration and control group, completed this survey. Within in-line filtration group, 97.3% of patients were satisfied/strongly satisfied; if compared with previous experiences on short peripheral venous cannulation, 11% of them recognised in-line filtration as a relevant causative factor in determining their satisfaction. Among patients within the control group, 93.2% were satisfied/strongly satisfied, although up to 30% of them had experienced postoperative phlebitis. At the qualitative interview, they recognised no difference than previous experiences on short peripheral venous cannulation, and mentioned postoperative phlebitis as a common event that 'normally occurs' during a hospital stay. Conclusion: In-line filtration is cost-effective in preventing postoperative phlebitis, and it seems to contribute to increasing patient satisfaction and reducing short peripheral venous cannulation–related discomfort